Determination of Selected Polycyclic Aromatic Compounds in Particulate Matter Samples with Low Mass Loading: An Approach to Test Method Accuracy. (27th July 2017) - García-Alonso, Susana; Pérez-Pastor, Rosa María; Archilla-Prat, Víctor; Sanz-Rivera, David; Rojas-García, Enrique; Aragón-Urrengoetxea, Gaizka; Rodríguez-Maroto, Jesús Javier
Abstract : A miniaturized analytical procedure to determine selected polycyclic aromatic compounds (PACs) in low mass loadings (<10 mg) of particulate matter (PM) is evaluated. The proposed method is based on a simple sonication/agitation method using small amounts of solvent for extraction. The use of a reduced sample size of particulate matter is often limiting for allowing the quantification of analytes. This also leads to the need for changing analytical procedures and evaluating its performance. The trueness and precision of the proposed method were tested using ambient air samples. Analytical results from the proposed method were compared with those of pressurized liquid and microwave extractions. Selected PACs (polycyclic aromatic hydrocarbons (PAHs) and nitro polycyclic aromatic hydrocarbons (NPAHs)) were determined by liquid chromatography with fluorescence detection (HPLC/FD). Taking results from pressurized liquid extractions as reference values, recovery rates of sonication/agitation method were over 80% for the most abundant PAHs. Recovery rates of selected NPAHs were lower. Enhanced rates were obtained when methanol was used as a modifier. Intermediate precision was estimated by data comparison from two mathematical approaches: normalized difference data and pooled relative deviations. Intermediate precision was in the range of 10–20%. The effectiveness of the proposed method was evaluated in PM aerosol samples collected with very low mass loadings (<0.2 mg) during characterization studies from turbofan engine exhausts.